Analisis Permukaan Benda Bubutan Dalam Pengujian Peforma Mesin Bubut Bemato Series 44378 - Putra, Muhammad Farhansyah; Erwansyah, Erwansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The performance of a machine significantly impacts the outcome on the workpiece. Therefore, regular maintenance of the machine is necessary. Over time, the machine's performance tends to decline. From the results of surface roughness testing on workpieces using variations in RPM and depth of cut parameters with constant feeding, the highest roughness value was 4.483 μm, produced by BU 27 and BU 30, with the highest roughness value of 2.694 μm. This study aims to test and verify the machine's performance level by examining the surface roughness values of ST41 workpieces. The research employs an experimental method, followed by processing the roughness data of machining results using a Bemato series 44378 lathe, involving 9 specimens and 2 replications.